2011
DOI: 10.1007/s00464-011-1819-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose antimicrobial prophylaxis in transoral surgical lung biopsy: a preliminary experience

Abstract: This study showed the feasibility of transoral thoracoscopy and surgical lung biospy in dogs. Moreover, single-dose prophylaxis with cefazoline in transoral surgical lung biopsy was found to be effective in preventing potential infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…We recently published a study demonstrating the successful performance of a minor thoracic procedure via a transoral approach in a canine model [11]- [13]. In line with these findings, our present study further demonstrated the safety and efficacy of the transoral approach in hemodynamic, inflammatory conditions.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…We recently published a study demonstrating the successful performance of a minor thoracic procedure via a transoral approach in a canine model [11]- [13]. In line with these findings, our present study further demonstrated the safety and efficacy of the transoral approach in hemodynamic, inflammatory conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Our group previously described the utilization of transtracheal thoracoscopy in 12 dogs; we encountered 3 cases of tension pneumothorax due to inadvertent injury to the lung during creation of a tracheal access site [20]. Recently, we have made significant progress in using a transoral route for surgical lung biopsy and pericardial window creation, without major intraoperative or postoperative complications [10]- [13]. Our findings suggest that a transoral approach can be used as a novel platform for studies of NOTES for intrathoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations